Ecology and Anthropology in Ecofeminist Theology - Naumowicz, Cezary (Studia Ecologiae et Bioethicae, 2010)
Ecofeminism is a current emerged in 1970, it’s a movement that sees a connection between the degradation of the natural world and the subordination and oppression of women. For some time problem of the ecological crisis and feministic analyses have been influencing theological reflection. Ecofeminist theology aims at combining ecology, feminism, and theology. Its main proponents are Rosemary Radford Ruether, Elizabeth Johnson, Sally McFague, Mary Grey, Anne Primavesi, Ivone Gebara, Elizabeth Green, and Elisabeth Moltmann-Wendel. Many authors make a hypothesis about responsibility of Jewish and Christian tradition for women suppression in patriarchal dualism and aim at reinterpreting some theological concepts.